2000
DOI: 10.1088/0953-8984/12/46/311
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-induced frequency shift of the Raman-active CuO2planar oxygen vibrational modes of Bi-2212 related to a change of the Cu-O bonding

Abstract: A change, with temperature, of the Cu-O or Bi-O bondings was previously suggested because irregular variations, with temperature, of the lattice parameters and of the electrical resistivity were observed in Bi-2212 crystals. To check the validity of this hypothesis, a study of the variation, with temperature, of the positions of Raman peaks associated with vibrations of the different kinds of O atom has been performed at room and at low temperature. It is shown here that the 285 cm −1 Raman peak (B 1g), associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…In Bi2201 and Bi2212 bismuth cuprates, some modes are characteristic of the atom to which oxygen is bonded [322] while the activation of forbidden modes is related to the ordering of the mobile oxygens [323,324]. Similarly, Fig.…”
Section: Analysis Of Localized Species and Sublatticesmentioning
confidence: 92%
“…In Bi2201 and Bi2212 bismuth cuprates, some modes are characteristic of the atom to which oxygen is bonded [322] while the activation of forbidden modes is related to the ordering of the mobile oxygens [323,324]. Similarly, Fig.…”
Section: Analysis Of Localized Species and Sublatticesmentioning
confidence: 92%
“…The initial finding of the absence of a phonon signature in the temperature dependence of the resistivity 1 and the small size of the isotope effect in the optimally doped cuprates 2 suggested that the electron-phonon interaction played a relatively unimportant role in these strongly-correlated materials. However, large isotope effects away from optimal doping, 2,3 significant phonon renormalization induced in the superconducting state, 4,5,6,7 and recent interpretations of ARPES data 8,9 continue to raise questions regarding the nature and role of the electron-phonon interaction in the high T c cuprates.…”
Section: Introductionmentioning
confidence: 99%